1999
DOI: 10.1523/jneurosci.19-23-10338.1999
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Role of Heat Shock Protein (Hsp) Molecular Chaperones in Polyglutamine Disease

Abstract: Polyglutamine (polygln) diseases are a group of inherited neurodegenerative disorders characterized by protein misfolding and aggregation. Here, we investigate the role in polygln disease of heat shock proteins (Hsps), the major class of molecular chaperones responsible for modulating protein folding in the cell. In transfected COS7 and PC12 neural cells, we show that Hsp40 and Hsp70 chaperones localize to intranuclear aggregates formed by either mutant ataxin-3, the disease protein in spinocerebellar ataxia t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
257
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(281 citation statements)
references
References 42 publications
20
257
2
1
Order By: Relevance
“…The suppression is particularly striking when HDJ-1, a member of the Hsp40 chaperone family, is overexpressed. Suppression of aggregate formation by Hsp40 has previously been demonstrated in in vitro models of polyglutamine disease (Cummings et al 1998;Chai et al 1999). Hsp40 is a cochaperone for Hsp70 and binds to and stimulates the ATPase activity of Hsp70 (Cyr et al 1994).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The suppression is particularly striking when HDJ-1, a member of the Hsp40 chaperone family, is overexpressed. Suppression of aggregate formation by Hsp40 has previously been demonstrated in in vitro models of polyglutamine disease (Cummings et al 1998;Chai et al 1999). Hsp40 is a cochaperone for Hsp70 and binds to and stimulates the ATPase activity of Hsp70 (Cyr et al 1994).…”
Section: Discussionmentioning
confidence: 90%
“…A role for HSPs in neurodegenerative diseases involving protein aggregation has been suggested by recent studies. Hsp40 and Hsp70 were found to localize to nuclear inclusions formed by mutant ataxin-1 and ataxin-3 in spinocerebellar ataxia types 1 and 3 (Cummings et al 1998;Chai et al 1999). Moreover, cell culture studies demonstrated that overexpression of HDJ-2 suppressed the aggregation of mutant ataxin-1, while that of HDJ-1 and HDJ-2 decreased aggregation of mutant ataxin-2, and a combination of HDJ-1 and Hsp70 prevented the aggregation of mutant androgen receptor in spinobulbar muscular atrophy (Chai et al 1999;Cummings et al 1998;Kobayashi et al 2000).…”
mentioning
confidence: 98%
“…One can envision that transfer of nonfoldable substrates to HSP70 would result in a fatuous ATP‐driven substrate binding and release, which may slightly delay aggregation but not prevent it. Indeed, in cells overexpression of HSP70s only marginally affects polyQ aggregation (Chai et al ., 1999; Rujano et al ., 2007), whereas in vivo HSP70‐mediated rescue of polyQ toxicity only occurs in the presence of semi‐soluble nuclear polyQ aggregates (Warrick et al ., 1999; Chan et al ., 2000; Cummings et al ., 2001). Thus, the different small HSPs with different affinities to substrates and HSP70s may have evolved to serve adequate processing of a broad spectrum of clients.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, both members of the Hsp40 family are associated with aggregates of glutamine-expansion proteins, and their overexpression suppresses polyQ aggregation (26,28). Interestingly, in the only study that directly compared the effects of HDJ1 and HDJ2, HDJ1 (the Sis1 homologue) had a much stronger effect than HDJ2 (the Ydj1 homologue) (43). Overexpression of Hsp70 in yeast had a stronger effect on HtQ72 and HtQ103 localization than any of the Hsp40 manipulations we tested.…”
Section: Discussionmentioning
confidence: 99%